The liver-derived exosomes stimulate insulin gene expression in pancreatic beta cells under condition of insulin resistance - Mahmoudi-Aznaveh, Azam; Tavoosidana, Gholamreza; Najmabadi, Hossein; Azizi, Zahra; Ardestani, Amin (Frontiers in Endocrinology, 2023)
Introduction: An insufficient functional beta cell mass is a core pathological hallmark of type 2 diabetes (T2D). Despite the availability of several effective pharmaceuticals for diabetes management, there is an urgent need for novel medications to protect pancreatic beta cells under diabetic conditions. Integrative organ cross-communication controls the energy balance and glucose homeostasis. The liver and pancreatic islets have dynamic cross-communications where the liver can trigger a compensatory beta cell mass expansion and enhanced hormonal secretion in insulin-resistant conditions. However, the indispensable elements(s) that foster beta cell proliferation and insulin secretion have yet to be completely identified. Exosomes are important extracellular vehicles (EVs) released by most cell types that transfer biological signal(s), including metabolic messengers such as miRNA and peptides, between cells and organs.We investigated whether beta cells can take up liver-derived exosomes and examined their impact on beta cell functional genes and insulin expression. Exosomes isolated from human liver HepG2 cells were characterized using various methods, including Transmission Electron Microscopy (TEM), dynamic light scattering (DLS), and Western blot analysis of exosomal markers. Exosome labeling and cell uptake were assessed using CM-Dil dye. The effect of liver cell-derived exosomes on Min6 beta cells was determined through gene expression analyses of beta cell markers and insulin using qPCR, as well as Akt signaling using Western blotting.Results: Treatment of Min6 beta cells with exosomes isolated from human liver HepG2 cells treated with insulin receptor antagonist S961 significantly increased the expression of beta cell markers Pdx1, NeuroD1, and Ins1 compared to the exosomes isolated from untreated cells. In line with this, the activity of AKT kinase, an integral component of the insulin receptor pathway, is elevated in pancreatic beta cells, as represented by an increase in AKT's downstream substrate, FoxO1 phosphorylation.This study suggests that liver-derived exosomes may carry a specific molecular cargo that can affect insulin expression in pancreatic beta cells, ultimately affecting glucose homeostasis.